Consideration of the interests of corporate stakeholders in addition to shareholders, in the approval of fundamental transactions under the companies act of 2008 - Mdlongwa, Gugulethu (University of the Witwatersrand, Johannesburg, 2024)
In an attempt to grow markets and generate profits, companies often engage in fundamental transactions, among other activities. Fundamental transactions may change the share value and structure of a company. They are listed in Chapter 5 of the Companies Act 71 of 2008 to include the disposal of a greater part of the company’s assets, mergers and amalgamations and schemes of arrangements. In this research, financial assistance in section 45 is considered as a fundamental transaction because when effecting it, companies rely on the requirements that apply to fundamental transactions in Chapter 5. In addition, when not effected accordingly, financial assistance may threaten the structure of a company, as it may cause fluctuation of securities. Before effecting a fundamental transaction, companies must adhere to the general requirements, which include a notice to shareholders, an approval from shareholders through a special shareholder’s resolution, and compliance with the solvency and liquidity tests. On implementation, dissenting shareholders may rely on the appraisal rights remedy in section 164. This right gives protection to dissenting shareholders by invoking a process of valuation of shares to ensure fair compensation for their shares in a fundamental transaction. In so far as the consideration of the interests of stakeholders is concerned, the Act does not adequately protect all stakeholders in fundamental corporate decisions. The issue of stakeholder inclusion in fundamental transactions has not received serious attention from scholars, a gap which may be attributed to the prevailing focus on the shareholder primacy approach in corporate governance. This has overshadowed the consideration of other stakeholders as well as the complexity of balancing the interests of different stakeholders within a company. These complexities may deter researchers from delving into this multifaceted issue. This paper addresses the gap and focuses on the effects of the implementation of fundamental transactions – the worst being corporate failure – as attributable to the non-consideration of stakeholders such as employees, customers, and investors in corporate decision-making. This study makes recommendations for the consideration of the interests of all key stakeholders, in addition to shareholders, in financial transactions. It seeks to address the undesirable effects on them and promote good corporate practice to achieve sustainability in the company, which is of common interest to all stakeholders.
A research report submitted in fulfillment of the requirements for the Master of Laws, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; stakeholder inclusion; shareholders; fundamental transactions; corporate governance; sustainability; SDG-8: Decent work and economic growth